A Decision Support System for Selecting High-Achieving Students at SDN 3 Montong Baan Using the Weighted Product Method - Izzul Anshori; Hendriawan Hadi; Lalu Puji Indra Kharisma; Sarita Sarita (Jurnal Krisnadana, 2026)
The assessment of outstanding students is essential to recognize their achievements and motivate them to improve their academic and non-academic abilities. At SDN 3 Montong Baan, the manual selection process is considered inefficient and tends to be subjective. This study aims to design a decision support system (DSS) using the Weighted Product (WP) method to evaluate students based on criteria such as academic grades, attendance, and personality. The system was developed using the Waterfall model through observation, interviews, and a literature review. As a result, the system can provide recommendations objectively, systematically, and transparently, helping the school make more accurate and efficient decisions in selecting outstanding students.